A Problem of Balto-Slavic Morphology: The Case of Endings of the Instrumental Singular and Plural of the Consonant and i-stem Inflections - Olsen, Birgit Anette (Scando-slavica, 2023)
The endings of the instrumental singular and plural in Balto-Slavic present a few problematic details. Apart from the selection of the dialectal variants in *-m- rather than *-bh- shared by Germanic, and the substitution of the original *-h 1 by an*-m-ending in the singular of the consonant and i-stems in both Baltic and Slavic, there is a discrepancy between the short i-vowel of the cognate languages and the Balto-Slavic evidence. Here a plural *-mīs with a long vowel must be assumed for both sub-branches, while Slavic presupposes a short-vocalic proto-form *-mĭ as opposed to Baltic where a long-vocalic *-mī may account for the entire material. The acute accentuation favours reconstructions with a laryngeal, i.e. sg. *-miH, pl. *-miHs, but where does this laryngeal come from, and why is it absent in the Slavic singular forms? It is here suggested that the starting point was the singular ending of the i-stems where the original *-ih 1 was contaminated with the *-m-ending *-mi, yielding *-mih 1 , further extended by *-s in the plural *-mih 1 -s. As a consequence of Kuiper's Law by which a post-vocalic word-final laryngeal was subject to facultative deletion we arrive at the variants *-mi (Slavic) and *-mih 1 > *-mī (Baltic).